2017
DOI: 10.1155/2017/2425645
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Surface Residual Stress Distribution of Cold Rolling Spline

Abstract: Residual stress is an important parameter in the evaluation of the performance of a cold rolling spline surface. However, research on cold rolling spline is rare. To improve the surface property of a spline, an involute spline is selected as the object of this study. The contour method for determining cold roll-beating residual stress involves measuring the force spatial distribution, performing a statistical analysis of the experimental results, establishing the parameters for the tooth profile for different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…The measured point interval was 0.2 mm × 0.2 mm, and the measurement trajectory was top-down, reciprocating. According to the coordinates of the measured points, the processing of the model was completed along the direction indicated in Figure 2(b), with the spline indexing the location of the residual stress at the extraction point interval of 0.25 mm [11][12][13][14]. The dimensions were h a = 2.20 mm, h d = 1.39 mm, and h f = 0.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The measured point interval was 0.2 mm × 0.2 mm, and the measurement trajectory was top-down, reciprocating. According to the coordinates of the measured points, the processing of the model was completed along the direction indicated in Figure 2(b), with the spline indexing the location of the residual stress at the extraction point interval of 0.25 mm [11][12][13][14]. The dimensions were h a = 2.20 mm, h d = 1.39 mm, and h f = 0.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…To characterize the cold roll-beating spline in production and processing and in comprehensive consideration of practical applications, the subjective entropy weight of the hardening degree and residual stress of the surface layer is determined using the cold roll-beating spline surface hardening specification matrix formula (9). According to (10), the subjective entropy weight is modified, and the synthesized entropy weight is obtained, as shown in Table 6.…”
Section: Establishment Of the Physical And Mechanical Performance Evamentioning
confidence: 99%
“…Yan et al established a cold rollbeating screw numerical simulation program and analyzed the microstructure deformation, hardness distribution, and hardened layer distribution of the screw through the analysis of stress field and strain field numerical simulation results and screw cold roll-beating forming test results; in addition, numerical simulations and experiments were combined to study the metal flow law in the process of screw cold rolling [8]. Ding et al improved the surface performance of cold rollbeating forming splines and studied the influence of cold rollbeating forming parameters on the distribution of residual stress and the depth distribution of the residual compressive stress in the tooth root, index circle, and tooth tip of a spline tooth profile by measuring the distribution of residual stress at the splitting circle of the cold roll-beating spline via the contour method [9]. In the application of Taguchi theory, to study the effect of the inclination angle, axial depth of cutting, spindle speed, and feed rate on the surface integrity of the workpiece during the milling process of the titanium coated carbide ball mill, Masmiati and Sarhan used the Taguchi optimization method to determine the degree of impact on the surface integrity of the workpiece, and the control parameters were determined with minimal variability; the results showed that the optimization results can improve the residual stress and microhardness in the inclined end milling process [10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the average value was obtained and used as the surface roughness value of the sample. [16,[18][19][20]. A walking wire was used to cut the machine, cutting a tooth from the cold roll-beating spline (shown in Figure 2) using bronze wire with a diameter of 0.1 mm at a feed rate of 2 mm/min with a feed rate of 0.5 mm/min along the shadow part of the spline, as shown in Figure 2.…”
Section: Surface Roughness Test Processmentioning
confidence: 99%
“…Cui et al [15] obtained the Hopkinson compression test under different strain rates and obtained the dynamic response characteristics of the microstructure and the influence of microstructure change on the macroscopic properties of materials at different strain rates. In terms of residual stress, Ding et al [16] took involute spline as the research object and used the contour method to measure the spatial distribution of residual stress and obtained the change rule between stress and depth.…”
Section: Introductionmentioning
confidence: 99%